The Second World War : Closing the Ring (Vol. 5) - Churchill, Winston S. (London Cassell and Company Ltd., 1952)
Covers the beginning of the summer of 1943 to the evening of June 5, 1943 with the great armada waiting for the historic landing on June 6.
Include Maps, Appendices and Index.
Keywords: World War (1939-1945) -- Churchill, Winston, 1874-1965 -- Italy -- Allied Occupation of Italy (1943-1947) -- Great Britain -- Europe -- Military campaigns -- Diplomatic history